Lumnitzera racemosa, White Flowered Black Mangrove - Natalia Medina-Irizarry; Michael G. Andreu; Stephen Enloe (EDIS)
This publication provides an in-depth profile of Lumnitzera racemosa for the use of interested laypersons with some knowledge of biology as well as academic audiences.